Answer:
Step-by-step explanation:
1). f(x) = 3x⁵
Step - 1
Convert the given function in the form of an equation.
y = 3x⁵
Step - 2
Interchange x by y.
Step - 3
Solve the equation for y
x = 3y⁵
y⁵ = [tex]\frac{x}{3}[/tex]
[tex]y=\sqrt[5]{\frac{x}{3}}[/tex]
Step - 4
Convert the equation into function.
[tex]f^{-1}(x)=\sqrt[5]{\frac{x}{3}}[/tex]
Correct.
2). f(x) = 3x + 7
Step - 1
y = 3x + 7
Step - 2
x = 3y + 7
Step - 3
3y = x - 7
y = [tex]\frac{1}{3}(x-7)[/tex]
Step - 4
[tex]f^{-1}(x)=\frac{1}{3}(x-7)[/tex]
Correct.
3). f(x) = 6 + 4x³
Step - 1
y = 4x³ + 6
Step - 2
x = 4y³ + 6
Step - 3
y = [tex]\sqrt[3]{\frac{1}{4}(x-6)}[/tex]
Step - 4
[tex]f^{-1}(x)=\sqrt[3]{\frac{1}{4}(x-6)}[/tex]
Incorrect.